2021
DOI: 10.14238/pi61.1.2021.46-52
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of the COVID-19 pandemic on doctors’ children: are we heading towards a mental health pandemic?

Abstract: Background The coronavirus pandemic (COVID-19) may affect the behavior of children. Non infected children of doctors seem to be susceptible to psychosocial health disorders. Objective To assess the psychosocial impact of the COVID-19 pandemic on children of doctors. Methods This questionnaire-based survey filled up by doctors was done with the Pediatric Symptom Check List-17 (PSC-17) to assess the psychosocial impact of the COVID-19 pandemic on doctors’ children aged 10-15 years with no clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Additionally, they found that the emotional benefits of exercise were curbed by lowered physical activity associated with increased screen time. Parents in Omer et al’s (2021) study considered increased screen time for their children to be “a matter of great concern” (p. 50). Chen et al (2021) found an increase in Internet gaming addiction after the beginning of the pandemic, which was significantly correlated with rates of depression, anxiety, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they found that the emotional benefits of exercise were curbed by lowered physical activity associated with increased screen time. Parents in Omer et al’s (2021) study considered increased screen time for their children to be “a matter of great concern” (p. 50). Chen et al (2021) found an increase in Internet gaming addiction after the beginning of the pandemic, which was significantly correlated with rates of depression, anxiety, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…A prosperous socioeconomic environment is naturally conducive to the development of arts and crafts and provides a material basis for their development. Only arts and crafts that penetrate deeply into people's lives can develop harmoniously in the social environment, so that their artistic personality can gain vitality and win people's consensus [18][19][20][21].…”
Section: Arts and Crafts Designmentioning
confidence: 99%